Avaliação do padrão de metilação dos genes ESR1, ESR2 e PGR nas linhagens celulares derivadas do câncer de mama - Baroni, Mirella [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Breast cancer has received an increasing attention because it is one of the most common cancer type and a leading cause of morbity and mortality among women worldwide. This disease has been considered as a heterogeneous condition, demonstrating a large spectrum of clinical and histopathological variability. In the last two decades, several studies have been conducted to identify new molecular markers of cancer cells, including the alterations of DNA methylation, which is the major epigenetic mechanism associated with the control of gene expression. The hypermethylation of promoter-associated CpG islands contributes to the loss of function of several cancer-related genes, including those encoding to the estrogen receptor (ESR) and progesterone receptor (PGR). This study aimed to determine the methylation patterns of CpG islands of the genes encoding the estrogen receptor α (ESR1 gene, promoters A and B), estrogen receptor β (ESR2 gene) and progesterone receptor (PGR gene, promoter A and B) in 15 cell lines derived from breast cancer. The DNA methylation analysis was based on the “Methylation Specific-Polymerase Chain Reaction” (MSP), which provides a qualitative assessment of the methylation status of a specific CpG island. The results revealed heterogeneous data: the promoter region of ESR1A showed complete methylation in one cell line (BT549) and only two cell lines showed partial methylation (MDA-MB-231 and MDA-MB-453), while the others lineages presented unmethylated alleles. The promoter region of isoform ESR1B was unmethylated in the cell lines BT549, SKBR3 and T47D; partial methylation were observed in the cell lines MDA-MB- 231, MCF-7 and ZR-75-30, while the others cell lines presented complete methylation. All lineages showed complete or partial methylation of the ESR2 gene. The methylation pattern of the promoter A of the PGR ...(Complete abstract click electronic access below)

O câncer de mama tem ganhado cada vez mais atenção por ser uma das neoplasias mais comuns e a principal causa de morbidade e mortalidade entre as mulheres no mundo. É uma doença heterogênea e de grande variabilidade clínica e histopatológica. Nas ultimas duas décadas, diversos estudos foram realizados buscando identificar as alterações moleculares, entre elas as que envolvem mudanças dos padrões de metilação do DNA, principal mecanismo epigenético, que está associado com o controle da expressão gênica. A hipermetilação das ilhas CpG localizadas em regiões promotoras contribui para a perda da função de vários genes relacionados com o câncer, incluindo os que codificam o receptor de estrógeno (ESR) e o receptor de progesterona (PGR). Esse projeto teve como objetivo analisar em 15 linhagens celulares derivadas de câncer de mama o padrão de metilação das ilhas CpG dos genes que codificam os receptores de estrógeno α (gene ESR1, promotores A e B), estrógeno β (gene ESR2) e progesterona (gene PGR, promotores A e B) e comparar com os dados existentes na literatura. Para isso utilizou-se a técnica de “Methylation-Specific- Polymerase Chain Reaction (MSP)”, a qual oferece uma avaliação qualitativa do estado de metilação das ilhas CpG. Os resultados obtidos revelaram dados heterogêneos, para a isoforma ESR1A observou-se somente uma linhagem com metilação total (BT549) e somente duas apresentaram metilação parcial (MDA-MB-231 e MDA-MB-453), enquanto as demais linhagens não apresentaram metilação nessa região. A região promotora ESR1B não apresentou metilação nas linhagens BT549, T47D e SKBR3, as linhagens que apresentam metilação parcial foram MDA-MB-231, MCF-7 e ZR-75-30, as demais linhagens apresentaram apenas alelos metilados (metilação completa). Todas as linhagens apresentaram metilação completa ou ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Genetica humana; Mamas - Cancer; Receptores hormomais; Estrogenos - Receptores; Progesterona